Using checklist and what if analysis for inspection fire pump room at the Faculty of Applied Science Building, KMUTNB - Nakkam Teravuti; Piyamongkala Kowit (E3S Web of Conferences)
The inspection and analysis of the qualitative for the fire protection system of the Faculty of Applied Science Building at King Mongkut’s University of Technology North Bangkok (KMUTNB) was surveyed by a standard checklist. Using the method of consideration according to the Regulations of the Building Control Act, the investigation examined six items of the fire pump room. Then, the risk assessment was observed by a what-if analysis. There were two non-critical items that should be improved including emergency lights and smoke detectors. Therefore, the fire protection system in the Faculty of Applied Sciences Building KMUTNB is ready to operate in the event of a cause of fire because the basic equipment have been estimated to be sufficient to use and in a state of high readiness.